ANALISIS YURIDIS TERHADAP KEDUDUKAN PENGADILAN PAJAK SEBAGAI PENGADILAN KHUSUS DI LINGKUNGAN PERADILAN TATA USAHA NEGARA - Budi Ispriyarso (Masalah-Masalah Hukum, 2014)
Regarding the position of the Tax Court in the judicial system in Indonesia there is fundamental difference between Law No. 14 of 2012 and other legislation (Law on Judicial Power, Law on State Administrative Court and Law on State Administrative Court). Under Law No. 14 of 2012, it implies that status of the Tax Court beyond the four court as stipulated in the Law on Justice Power. While the statutory, the law on judicial Power, the law of the State Administrative Court and the Law on General Provisions and Tax Procedures, the position of the Tax Court as a Special Court in the State Administrative Court. Juridical controversy will certainly be legal uncertainty about the position of the Tax Court. This will be examined in this paper